The Relationship of Participation in Early Childhood Education Activities at the Integrated Healthcare Center Park with the Development of Toddler Children in NgadiRenggo Village, Pogalan District, Trenggalek Regency - Aziza Ainur Qamaria; Nur Yeny Hidajaturrokhmah (Open Access Health Scientific Journal, 2021)
Background: Integrated healthcare center park is a government effort in optimizing Integrated healthcare center activities so that they do not only carry out monitoring functions but are also promotive efforts to stimulate child growth and development better, but in fact there are still many children who have not participated in Taman Integrated healthcare center either due to limited facilities and there are still many parents who doubt the benefits. Method: The design of this study was observational with a cross sectional approach. The population of this study were all toddlers in Ngadirenggo Village, Pogalan District-Trenggalek totaling 399 toddlers, with a proportioned random sampling technique obtained a sample of 40 respondents. The independent variable is the participation of Taman Integrated healthcare center with the dependent variable being child development. Data analysis using Spearman rank test at=0.05. Results: The results showed that all respondents who participated in Taman Integrated healthcare center had the appropriate category development, namely 8 respondents (100.0%) and most of the respondents who did not participate in Taman Integrated healthcare center had development in the appropriate category, namely 22 respondents (55.0%). The results of the analysis showed that there was a relationship between participation in Early Childhood Education Programs activities at the Integrated healthcare center Park with the development of children under five in Ngadirenggo Village, Pogalan District, Trenggalek Regency (p = 0.005 < = 0.05). Conclusion: Children who participate in the integrated healthcare center park will get better monitoring of growth and development, besides that they will also get developmental stimulation through group activities. Existing play and learning activities are useful in honing children's development so that children who participate in Integrated healthcare center parks tend to have more appropriate developments